Merytokracja czy „elity odpowiedzialnościowe”? Ewangelicka interpretacja zagadnienia elit społecznych - Kopiec, Piotr (Annales. Etyka w Życiu Gospodarczym, 2015)
The notion of meritocracy is among the keywords used in order to describe thecontemporary world. It has become more and more an inherent concept of anorder whose main factors are said to be globalization as well as the impact of freemarket philosophy on society and culture. The concept of meritocracy considersthe nature of elites. On the one hand, meritocratic elites are taken from groupsselected for their merits and competences, but on the other hand they avoid theirresponsibility towards society and culture. Amongst many counterproposals itseems worthwhile to present the evangelical concept of elites which is deeplyembedded in evangelical social teaching. Evangelical theology introduces in itssocial discourse the notion of the responsibility elites. According to evangelicaltheologians, the key task to overcome the growing social, economic and culturalcrisis of today may be found in the rehabilitation of the notion of common good.Interpreted from a sociological as well as theological standpoint, responsibilityelites play an important role when spreading the concept of the common good.The article presents theological guidelines of evangelical teaching on elites as wellas evangelical proposals concerning the issue collating them with the broad diagnosisof the meritocratic elites.